БАГАТОВИМІРНІСТЬ ВТІЛЕНЬ СЮЖЕТУ ТУРАНДОТ В ЖАНРІ ТЕАТРАЛЬНОЇ МУЗИКИ - Ванг Юй (World Science, 2019)
The article deals with the historical projection of the 300-year-old path of the Turandot image in the genre of theatrical music. After completing all the stages of European exoticism in Chinese subjects, Turandot was embodied in the main stages of the development of musical drama - from the baroque French Fair Theater Fory Saint-Lauren (Le Sage / d’Orneval for the first time analyzed music by J.C. Gillіer) through the pre-classical model of Italian folk (K. Gozzi) to the concept of German romanticism (F. Schiller ‒ F. Destush, K.M. Weber, W. Lyahner), oriental readings of the early modern days: neoclassical (F. Buzoni), symbolist (W. Ferst), primitive-naive (Y. Vakhtangov), psychologically-expressionistic (W. Stenhammar), household-entertaining variants (Broadway Theater) and complex multicomponent phenomena of the second half of the twentieth century, embodied in the "epic theater" (B. Brecht / H. D. Hosalla, Y. Lakner, A. Schnitke) and means "Theater of absurd" (W. Hilderschmayer), based on postmodernistic parameters of hybrid genre formations in Ukrainian culture (M. Denisenko, I. Uryvskiy) in the globalized reference of intercultural communication of the beginning of the third millennium.